A Broad‐Spectrum Catalytic Amidation of Sulfonyl Fluorides and Fluorosulfates. Issue 13 (8th February 2021) - Wei, Mingjie; Liang, Dacheng; Cao, Xiaohui; Luo, Wenjun; Ma, Guojian; Liu, Zeyuan; Li, Le
Abstract: A broad‐spectrum, catalytic method has been developed for the synthesis of sulfonamides and sulfamates. With the activation by the combination of a catalytic amount of 1‐hydroxybenzotriazole (HOBt) and silicon additives, amidations of sulfonyl fluorides and fluorosulfates proceeded smoothly and excellent yields were generally obtained (87–99 %). Noticeably, this protocol is particularly efficient for sterically hindered substrates. Catalyst loading is generally low and only 0.02 mol % of catalyst is required for the multidecagram‐scale synthesis of an amantadine derivative. In addition, the potential of this method in medicinal chemistry has been demonstrated by the synthesis of the marketed drug Fedratinib via a key intermediate sulfonyl fluoride 13 . Since a large number of amines are commercially available, this route provides a facile entry to access Fedratinib analogues for biological screening. Abstract : 1‐Hydroxybenzotriazole (HOBt) was identified as an efficient nucleophilic catalyst to activate sulfonyl fluorides and fluorosulfates for a broad‐spectrum, catalytic amidation to prepare various sulfonamides and sulfamates, including sterically hindered ones. The potential of this methodology in medicinal and process chemistry has been demonstrated by multidecagram‐scale synthesis of an amantadine derivative and synthesis of the drug Fedratinib.